Varicella-zoster virus recapitulates its immune evasive behaviour in matured hiPSC-derived neurospheroids - Govaerts, Jonas; Van Breedam, Elise; De Beuckeleer, Sarah; Goethals, Charlotte; D’Incal, Claudio Peter; Di Stefano, Julia; Van Calster, Siebe; Buyle-Huybrecht, Tamariche; Boeren, Marlies; De Reu, Hans; Paludan, Søren R.; Thiry, Marc; et al. (Frontiers in Immunology, 2024)
Varicella-zoster virus (VZV) encephalitis and meningitis are potential central nervous system (CNS) complications following primary VZV infection or reactivation. With Type-I interferon (IFN) signalling being an important first line cellular defence mechanism against VZV infection by the peripheral tissues, we here investigated the triggering of innate immune responses in a human neural-like environment. For this, we established and characterised 5-month matured hiPSC-derived neurospheroids (NSPHs) containing neurons and astrocytes. Subsequently, NSPHs were infected with reporter strains of VZV (VZVeGFP-ORF23) or Sendai virus (SeVeGFP), with the latter serving as an immune-activating positive control. Live cell and immunocytochemical analyses demonstrated VZVeGFP-ORF23 infection throughout the NSPHs, while SeVeGFP infection was limited to the outer NSPH border. Next, NanoString digital transcriptomics revealed that SeVeGFP-infected NSPHs activated a clear Type-I IFN response, while this was not the case in VZVeGFP-ORF23-infected NSPHs. Moreover, the latter displayed a strong suppression of genes related to IFN signalling and antigen presentation, as further demonstrated by suppression of IL-6 and CXCL10 production, failure to upregulate Type-I IFN activated anti-viral proteins (Mx1, IFIT2 and ISG15), as well as reduced expression of CD74, a key-protein in the MHC class II antigen presentation pathway. Finally, even though VZVeGFP-ORF23-infection seems to be immunologically ignored in NSPHs, its presence does result in the formation of stress granules upon long-term infection, as well as disruption of cellular integrity within the infected NSPHs. Concluding, in this study we demonstrate that 5-month matured hiPSC-derived NSPHs display functional innate immune reactivity towards SeV infection, and have the capacity to recapitulate the strong immune evasive behaviour towards VZV.